2019
DOI: 10.21776/ub.jkb.2019.030.03.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Green Coffee Beans Extract Ointments for Wound Healing

Abstract: <p>Some interventions, such as coffee powder, are applied on wound to facilitate healing process. Coffee has several properties that can facilitate wound healing. Application of Robusta coffee bean ointment 22.5 % on full thickness wound could increase  fibroblast. Povidone iodine 10% has remained popular as wound antiseptic. This study aimed to evaluate the effect of green coffee bean extract in lower concentration for healing wound in rats. This study used male Sprague Dawley rats, 10 rats in each grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Cytotoxicity studies were compared to green coffee extract. Many studies indicate that green coffee has beneficial effects on skin cells [ 16 , 44 ]. In addition, green coffee extract could increase wound contraction and accelerate wound healing [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytotoxicity studies were compared to green coffee extract. Many studies indicate that green coffee has beneficial effects on skin cells [ 16 , 44 ]. In addition, green coffee extract could increase wound contraction and accelerate wound healing [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies indicate that green coffee has beneficial effects on skin cells [ 16 , 44 ]. In addition, green coffee extract could increase wound contraction and accelerate wound healing [ 44 , 45 ]. Due to the small amount of research on the fermentation of green coffee beans with kombucha, we wanted to check the effect of the obtained ferments on skin cells.…”
Section: Resultsmentioning
confidence: 99%
“…Similar in vitro study with fibroblast/NIH3T3 cell has not been reported, but a research in green coffee beans extract showed that 15% extract was not not cytotoxic, moreover it could induce proliferation of fibroblast. (11) The basic migration cycle includes expansion, formation of stable attachments, translocation of cells, release of adhesions and retraction in other parts of the cell. (12) The migration is an important factor for tissue regeneration of various part of human.…”
Section: Discussionmentioning
confidence: 99%